Geography, Facilities, and Promotional Strategies Used to Encourage Indoor Tanning in New York City - Brouse, Corey H. (J Community Health, 2011)
There is emerging evidence for the relationship between indoor tanning and melanoma. Eighty-five indoor tanning facilities in New York City were observed to determine number of tanning machines, pricing, promotions, products, and hours. Census data by zip code was used to determine population density, gender, race, age, percent living in poverty, percent unemployed, and percent college educated of areas in which tanning facilities were located. Pricing varied by the type of machine, number of sessions purchased, and single versus bundled sessions. Facilities were located in areas that had greater population density and slightly greater median age. Compared with the zip code areas with no facilities, those with tanning facilities had a higher proportion of white residents; a lower proportion of residents living in poverty and unemployed; and a higher proportion of residents with a college education. Our data suggest that the strategic location of facilities and promotions used in NYC seek to maximize patronage by those with comparatively high levels of income and education and who may be more influenced by the social desirability of artificial tanning. Long-term interventions aimed at changing social norms regarding tan skin are needed.